Development of a land-sea coordination degree index for coastal regions of China. (1st November 2022) - Gao, Jinzhu; An, Taitian; Shen, Jiawen; Zhang, Kuncheng; Yin, Yue; Zhao, Rui; He, Guangshun; Hynes, Stephen; Jattak, Zafar Ullah
Abstract: Land-sea coordination is a key principle of current national spatial planning and coastal spatial planning in China. In order to provide data that will serve for marine policy decision-making purposes this research develops innovatively a model to measure the degree of land-sea coordination and proposes a four-dimensional index system that includes economic development, resource utilization, ecological environment, and social livelihood. Tianjin and Shanghai are selected as the research areas. The results indicate that the degree of land-sea coordination in both Tianjin and Shanghai has increased over the reference period. In Tianjin, the land system efficiency was higher than that of the marine system, and urban development was dominant for land with moderate coordination. The efficiency of land and sea system were basically uniform in Shanghai, where urban progress remains moderately coordinated with a two-way development of land and sea. Land-sea coordination degree index can be used in the compilation and evaluation of territorial spatial planning and coastal zone special planning, and even the index itself can be used as the phased evaluation result after the implementation of spatial planning.